Donald Trump dan Berita Imigran di Aljazeera.com dan Foxnews.com - Anggoro, Ayub Dwi; Purwati, Eli; Hilman, Yusuf Adam (FISIP Universitas Atma Jaya Yogyakarta, 2018)
Donald Trump’s policy on immigrants has been a controversy. The controversy culminated when the policy was reported by the media, such as Foxnews.com and Aljazeera.com. This study aims to compare news framing in both media, especially the application of ideology and political economic of media, as an effort to get objective and neutral reporting. This research uses qualitative approach with framing analysis method of Zhongdang Pan and Gerald M. Kosicki. The results show that framing by Foxnews.com and Aljazeera.com is in favor of the interests of media owners, namely Rupert Murdoch and the government of Qatar.